2006
DOI: 10.1007/s00383-005-1632-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory laparoscopy for recurrent right lower quadrant pain in a pediatric population

Abstract: Recurrent or chronic abdominal pain can be a challenging problem when conventional diagnostic studies fail to identify the cause. It is estimated that up to one-third of children suffer from abdominal pain, and in this population recurrent pain can be even more challenging. Although recurrent right lower quadrant (RLQ) or periumbilical pain may be attributed to chronic appendicitis, this diagnosis remains controversial. Our aim was to evaluate pediatric patients who had undergone laparoscopic exploration for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
(18 reference statements)
1
14
0
Order By: Relevance
“…Early laparoscopy is not the treatment of choice in these patients and many surgeons decide to explore when common tests and observation are not able to differentiate medical versus surgical treatment plan [4].…”
Section: Introductionmentioning
confidence: 99%
“…Early laparoscopy is not the treatment of choice in these patients and many surgeons decide to explore when common tests and observation are not able to differentiate medical versus surgical treatment plan [4].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of laparoscopy in these patients is that they can be provided therapy in the same setting. Kolts et al,3 in their study of 44 children with chronic lower abdominal pain, showed resolution of symptoms in 70.5% of cases after appendectomy. Similarly, in our series complete or partial relief was obtained in 77.7% of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Similar views have been echoed in other studies addressing this issue. [6][7][8] Gorenstein series has clearly shown that in a significant number of cases the pain subsides even if the removed appendix is normal on histology. 5 In our series 5 cases had a normal appendix on histology.…”
Section: Discussionmentioning
confidence: 99%